When violence works postconflict violence and peace in Indonesia - Barron, Patrick 1977- (Cornell University Press, 2019)
Illuminates why postconflict areas so often continue to see violence and what can be done to consolidate peace in areas emerging from large-scale violent confllicts-- --Provided by publisher